Evaluasi Beberapa Kultivar Padi Gogo Asal Kalimantan Timur untuk Ketahanan terhadap Aluminium Menggunakan Metode Kultur Hara - , Rusdiansyah; Neni Rohaeni; , Trikoesoemaningtyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
Twenty four upland rice cultivars from East Kalimantan and control cultivar were evaluated for tolerance to aluminium using nutrient culture with two treatments of 0 ppm and 45 ppm AI. Result showed that eight cultivars (Pimping, Ketan Hitam, Mayas, Padi Bulu, Popot, Siam Kuning, Ketan Merah, Serai) have PAR > 0.5 and were categorized as tolerant cultivar, the other 16 cultivars were categorized as suceptable. Three tolerant cultivars: Pimping, Ketan Merah and Mayas. even have PAR higher than a control, Krowal. Key words: Rice, AI, PAR, Nutrient